Trust in virtual team software development - Che Mohd. Yusoff, Rasimah (American Scientific Publishers, 2014)
Due to the growth of communication technologies, virtual teams have become more common in software industry. However, virtual teams are still having issues in developing and building trust among their team members across the space, time and culture. This study was conducted to determine the factors that affect trust for virtual team in software development. A trust model was proposed which consist of ability, benevolence, integrity and computer-mediated communication. The relationships between ability, benevolence, integrity and computermediated communication towards trust was analyzed. The study used a quantitative method and the survey data was collected from 80 members of virtual teams in IT departments from different organizations. The findings suggested that ability and integrity significantly have positive relationships with trust. Also, virtual teams’ trust is negatively associated with computer-mediated communication. There is no significant impact from benevolence to trust in virtual team.